Analisis Sentimen Terhadap KPU 2024 Berdasarkan Tweet Media Sosial Twitter Menggunakan Algoritma Naïve Bayes - Dion Parisda Ray; Firman Noor Hasan; Ahmad Rizal Dzikrillah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
The development of technology is currently very rapid making the dissemination of information faster, the dissemination of information is very easy to get on social media such as Twitter. Twitter social media itself provides features for its users to be able to send and read information in the form of text or video. Elections are a very important moment for the Indonesian people in choosing leaders, in this case the "2024 KPU" as the organizer is expected to be able to run the elections so that they run well. Twitter data collected with the keyword "KPU 2024" obtained a total of 3057 datasets, followed by a cleansing process which produced 715 datasets. The aim of this research is to find out how many positive and negative tweets comments and to indicate the accuracy of the implementation of the Naïve Bayes method. The accuracy results given by the Naïve Bayes algorithm are 67.13% with a precision of 66.04% and a recall of 100.00%. This research was conducted to see public sentiment towards the "2024 KPU" later. Evaluation results in the confusion matrix obtained true positives of 457 and true negatives of 235